Development and validation of a parametric human mandible model to determine internal stresses for the future design optimization of maxillofacial implants. (January 2022) - Wieja, Franziska; Jacobs, Georg; Stein, Sebastian; Kopp, Alexander; van Gaalen, Kerstin; Kröger, Nadja; Zinser, Max
Abstract: Large segmental mandible bone defects still represent a challenge for endogenous regeneration. Despite the bone's capacity to heal in many clinical situations, bone defects over a critical size do not heal spontaneously. An emerging treatment of critically sized mandibular defects is the implantation of individually manufactured scaffolds consisting of biodegradable magnesium alloys. Biomedical engineers faced the challenge of developing a scaffold structure that not only provides sufficient stability, but also stimulates and promotes bone growth while considering the degradation of the magnesium alloy. The porosity of the scaffold must also support bone ingrowth and neovascularization. For an optimal design and subsequent structural optimization knowledge of external load cases is essential. However, currently the muscle and joint forces of the mandible cannot be measured directly. The aim of our study was therefore the development of a parametric human mandible model to determine the relevant boundary conditions for the subsequent structural optimization of individual jawbone implants. Using a model-based approach, determining the essential external load of the mandible as a function of the age and sex of a patient individually and the realistic simulation of the mechanical stress for patient-specific loads and anatomies has been realized. The developed model is successfully validated by evaluating the deformations and stresses of the lower jaw of a possible patient and comparing them with the results of dental research. Based on the results of the modelling, in a subsequent optimization process section forces at the interface between the bone tissue and jawbone implant can be determined and used to optimize the design of the jawbone implant. Graphical abstract: Image 1 Highlights: Customized scaffolds can be optimized for the reconstruction of critical bone defects. For optimization, knowledge of the mechanical boundary conditions is essential. Currently the internal muscle and joint forces cannot be measured directly. A model of the human mandible has been developed, using a model-based approach. It considers individual anatomy and masticatory function to determine the boundary conditions.